Effects of climatic changes on olive fly, Bactrocera oleae (Rossi) population dynamic with respect to the efficacy of its larval parasitoid in Egyptian olive trees - Abd El-Salam, Ahmed Mohamed Ezzat (2021)
The results exhibited that the olive trees in the coast governorate were more susceptible to the olive fly than the inner governorate. The parasitism percentage was recorded 41.7 and 46.4% at the beginning of the seasons 2016 and 2017, respectively in El-Fayoum Governorate. In El-Behera Governorate, the maximum parasitism percentage was recorded 49.5% (2016 season), while the 2017 season, the parasitism percentage was recorded 50.4%. The majority of the ordinary parasite was Psyttalia concolor in the two regions.